AUTOMATIC FISH GRILLER BASED ON TEMPERATURE CONTROLLER - Sagita Rochman; Roib Mukodah (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
The automatic fish grill is a tool that is very helpful for food vendors who are processed in a roasting manner. For now, conventional automatic grills that are already on the market have very expensive prices so that many traders still use manual fish grills which are less efficient in the process of doing them. The purpose of making this automatic fish grill design is to help human work to save more time and energy. The automatic fish roasting box is designed with heat absorbers in each layer, equipped with two racks, each measuring 50cm and also equipped with 2 250 watt heaters. From the test results using different types of carp with different weights, it shows that the automatic fish grill works well and gets a 100% percentage result with evenly cooked fish. The economical level of automatic fish grill has a good value, the whole design of automatic fish grill uses good quality materials and materials. For now, automatic roasters on the market have very expensive prices, this difference in price has made many traders not take full advantage of the technology. Because of this problem, researchers created an automatic fish grill based on a temperature controller, which is targeted at an inexpensive price, but can still be used safely and with maximum results. Thus, using a temperature controller-based automatic fish grill design can help simplify work to make it more efficient and safer.